Brand transgressions: How, when, and why home country bias backfires - Davvetas, Vasileios; Ulqinaku, Aulona; Katsikeas, Constantine S. (Journal of the Academy of Marketing Science, 2024)
AbstractDespite heightened interest in brand transgressions among academics and practitioners, the literature remains silent about the influence of a brand’s origin on consumer responses to brand misconduct. This leaves managers unaware of how to adapt post-transgression recovery strategies at home and abroad. Contrary to the in-group country bias literature, we theorize an “origin-backfire” effect: consumers forgive domestic brand transgressions less. Analyzing experimental, social media, and secondary-longitudinal data, we find that consumers treat domestic brand transgressors as home-country traitors deserving punishment. Social identity threats mediate this effect and consumer ethnocentrism attenuates it. Transgressions’ damage on brand reputation and value is larger and takes longer to recover from in domestic markets. Managers can alleviate post-transgression backlash through communication framing that construes the transgression as a response to intergroup threats (in foreign markets) and through collective compensation strategies (in domestic markets). The findings reveal cross-national variability in transgressions’ experience, impact, and recovery and inform post-transgression repair strategies.